1996
DOI: 10.1002/etc.5620151019
|View full text |Cite
|
Sign up to set email alerts
|

Dietary accumulation of C12‐ and C16‐chlorinated alkanes by juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: Abstract-DietaryC analysis of fish tissue extracts revealed that the chlorinated alkane mixtures were selectively biotransformed with certain unknown components persisting in tissues. Lower chlorinated alkanes had greater proportions of polar 14 C, which implies greater metabolism of these compounds. Highly chlorinated, short-carbon-chain (C 10-13 ) alkanes and lower chlorinated, medium-carbon-chain (C 14-18 ) alkanes appear to have the greatest potential for biomagnification among CP components. No reduced gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 33 publications
(78 reference statements)
3
58
1
Order By: Relevance
“…On the other hand, the same study reported relatively high levels in terrestrial herbivores. Half-lives of PCAs in fish are also generally shorter than those for PCBs, toxaphene, and chlordane components when studied under identical conditions [80,81]. There is a need for studies of the biomagnification of PCAs in aquatic and terrestrial food webs in order to understand pathways of exposure and the importance of carbon chain length and Cl content.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the same study reported relatively high levels in terrestrial herbivores. Half-lives of PCAs in fish are also generally shorter than those for PCBs, toxaphene, and chlordane components when studied under identical conditions [80,81]. There is a need for studies of the biomagnification of PCAs in aquatic and terrestrial food webs in order to understand pathways of exposure and the importance of carbon chain length and Cl content.…”
Section: Discussionmentioning
confidence: 98%
“…). SCCPs appear to be persistent in the environment and have the potential to strongly accumulate in biota (Persistent Organic Pollutants Review Committee, 2010;Fisk et al, 1996Fisk et al, , 1998Houde et al, 2008;Iozza et al, 2008). The International Agency for Research on Cancer has classed SCCPs as group 2B compounds (International Agency for Research on Cancer, 1990), and SCCPs are also classified as Carc.…”
Section: Introductionmentioning
confidence: 98%
“…Short-chain chlorinated paraffins (SCCPs, C 10 -C 13 ) can affect the liver, thyroid hormone system, and kidneys, e.g., by inducing hepatic enzymes and hyperactivity in the thyroid, which can lead to both acute and chronic toxic effects with long-term exposure (UNEP/POPS/POPRC.8/6, 2012). Because of their potential for environmental persistence (Iozza et al, 2008), toxicity (Geng et al, 2015), bioaccumulation (Fisk et al, 1996;Houde et al, 2008;Ma et al, 2014b;Zeng et al, 2011b) and long-range atmospheric transport (Ma et al, 2014c;Vulykh et al, 2007), SCCPs have received widespread public attention. SCCPs were even included in Annex E of the Stockholm Convention by the persistent organic pollutants (POPs) Review Committee as a POP candidate in 2008 (UNEP/POPS/POPRC.3/ 20, 2008) since these properties are quite similar to those of legacy POPs (Poremski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%